The effect of supplementation of Lumbricus sp. extract in fermented foods for growth performance, body chemical composition, and hepatosomatic index of milkfish, Chanos chanos Forsskal, 1775 - Siti Aslamyah; Zainuddin Zainuddin; Badraeni Badraeni (Jurnal Iktiologi Indonesia, 2019)
The quality of feed can be improved by fermenting feedstuffs and supplementing with feed additives. This study aims to determine the effect of supplementation of Lumbricus sp. extract in fermented feed on growth performance, body chemical composition, and milkfish hepatosomatic index. Milkfish with an initial weight of 17.80 ± 0.20 g head-1, rearing with a density of 20 fish per hapa net measuring 1 m3 by 24 pieces. Hapa net is installed in a pond with a water level of ± 60 cm. Research was design in completely randomized design with two factors. The first-factor was supplementation method, namely Lumbricus sp. which sprayed on feed and mixed with feed ingredients. The second factor was the dose of Lumbricus sp. extract, namely 0, 100, 200 and 300 mL kg-1 of feedstuffs. The fish was reared for 50 days and fed with 5% of fish biomass per day with feeding frequency of 3 times i.e., morning, afternoon and evening. The results showed that the supplementation Lumbricus sp. extract has no significant effect on all parameters (P>0,05). However, the level dose of Lumbricus sp. extract supplementation in feed has a significantly effect (P<0.05) on absolute growth, relative growth, feed efficiency, and hepatosomatic index, but no significant effect (P>0,05) on survival and chemical composition of milkfish body. The best best of absolute growth (16.94±4.0 g), relative growth (48.71±5.77%), feed efficiency (40.74±10.3 %), and hepatosomatic index (1.5 ± 0.17) were found in the experiment of supplementation Lumbricus sp. extract mixed with feedstuffs at a dose of 300 mL kg1. The survival rate of milkfish was ranging from 68.33±29.3 to 91.,33±7.64%, while the body's chemical composition including protein levels, fat, ash, crude fiber, NFE / Nitrogen Free Extract, liver glycogen and muscle glycogen were 69.45±1.23 – 71.45±0.97%, 14.86±0.46 – 17.24±0.76%, 9.28±0.12 – 11.12±0.46%, 1.54±0.09 – 1.66 ± 0.13%, 1.33± 0.42 – 2.71±0.21%, 7,11±0,08 – 7,40±0,17mg g-1 and 6,13±0,44 – 6,45±0,40 mg g-1, respectively. Abstrak Kualitas pakan dapat ditingkatkan dengan memfermentasi bahan baku pakan dan suplementasi dengan aditif pakan. Penelitian ini bertujuan untuk mengkaji pengaruh suplementasi ekstrak Lumbricus sp. dalam pakan fermentasi terhadap kinerja pertumbuhan, komposisi kimiawi tubuh, dan indeks hepatosomatik ikan bandeng. Ikan bandeng dengan bobot awal 17,80±0,20 g ekor-1, dipelihara dengan kepadatan 20 ekor per hapa berukuran 1 m3 sebanyak 24 buah. Hapa dipasang di tambak dengan ketinggian air ± 60 cm. Penelitian didesain dengan rancangan acak lengkap dua faktorial. Faktor pertama adalah metode suplementasi, yaitu ekstrak Lumbricus sp. disemprot pada pakan dan dicampur dengan bahan baku pakan; sementarara faktor kedua adalah dosis ekstrak Lumbricus sp., yaitu 0, 100, 200, dan 300 mL kg-1 bahan baku pakan. Selama 50 hari pemeliharaan diberi pakan 5% bobot badan per hari dengan frekuensi tiga kali sehari yakni pagi, siang, dan sore. Hasil penelitian menunjukkan bahwa suplementasi tidak berpengaruh nyata (P>0,05) pada semua parameter. Namun, dosis suplementasi ekstrak Lumbricus sp. dalam pakan berpengaruh nyata (P<0,05) terhadap pertumbuhan mutlak, pertumbuhan relatif, efisiensi pakan, indeks hepatosomatik, tetapi tidak berpengaruh nyata (P>0,05) terhadap sintasan dan komposisi kimiawi tubuh ikan bandeng. Pertumbuhan mutlak (16,94±4,0 g), pertumbuhan relatif (48,71±5,77%), efisiensi pakan (40,74±10,37%), dan indeks hepatosomatik (1,50±0,17) terbaik ditemukan pada metode suplementasi ekstrak Lumbricus sp. yang dicampur dengan bahan baku pakan dengan dosis 300 mL/kg. Sintasan berkisar antara 68,33±29,3 - 91,33±7,64%, sedangkan kisaran komposisi kimiawi tubuh meliputi kadar protein (69,45±1,23 - 71,45±0,97%), lemak (14,86±0,46 - 17,24±0,76%), abu 9,28±0,12 - 11,12±0,46%), serat kasar (1,54±0,09 - 1,66±0,13%), BETN/Ba-han Ekstrak Tanpa Nitrogen (1,33±0,42 - 2,71±0,21%), glikogen hati (7,11±0,08 - 7,40±0,17 mg g-1) dan glikogen otot (6,13±0,44 - 6,45±0,40 mg g-1).